Functional characterization of 4 polymorphisms in promoter region of hepatic lipase gene. - van't Hooft, F; Lundahl, B; Ragogna, F; Karpe, F; Olivecrona, G; Hamsten, A (2000)
Hepatic lipase (HL) is a lipolytic enzyme involved in the metabolism of plasma lipoproteins, especially high density lipoproteins. Association studies have provided strong evidence for relations of common mutations in the promoter region of the HL gene to postheparin plasma HL activity and the plasma high density lipoprotein cholesterol concentration, but the functional relevance of these polymorphisms has not been evaluated to date. We analyzed the physiological significance of 4 common polymorphisms (-250G/A, -514C/T, -710T/C, and -763A/G, all in strong linkage disequilibrium) in the promoter of the HL gene by use of electrophoretic mobility shift assays and transient transfection studies in HepG2 cells. No consistent evidence was found for a significant contribution of any of these polymorphisms to the basal rate of transcription of the HL gene. These data suggest that the 4 polymorphisms in the promoter region of the HL gene are in linkage disequilibrium with >/=1 as-yet-unknown functional polymorphisms in the HL gene locus with a significant effect on HL metabolism and/or enzymatic activity.